Secluded WIMPs, dark QED with massive photons, and the galactic center gamma-ray excess - Fortes, E. C. F. S. [UNESP]; Pleitez, V. [UNESP]; Stecker, F. W. (Elsevier B.V., 2016)
We discuss a particular secluded WIMP dark matter model consisting of neutral fermions as the dark matter candidate and a Proca-Wentzel (PW) field as a mediator. In the model that we consider here, dark matter WIMPs interact with standard model (SM) particles only through the PW field of similar to MeV-multi-GeV mass particles. The interactions occur via a U(1)' mediator, V-mu', which couples to the SM by kinetic mixing with U(1) hypercharge bosons, B-mu'. One important difference between our model and other such models in the literature is the absence of an extra singlet scalar, so that the parameter with dimension of mass M-V(2) is not related to a spontaneous symmetry breaking. This QED based model is also renormalizable. The mass scale of the mediator and the absence of the singlet scalar can lead to interesting astrophysical signatures. The dominant annihilation channels are different from those usually considered in previous work. We show that the GeV-energy gamma-ray excess in the galactic center region, as derived from Fermi-LAT Gamma-ray Space Telescope data, can be attributed to such secluded dark matter WIMPs, given parameters of the model that are consistent with both the cosmological dark matter density and the upper limits on WIMP spin-independent elastic scattering. Secluded WIMP models are also consistent with suggested upper limits on a DM contribution to the cosmic-ray antiproton flux. Published by Elsevier B.V.
Keywords: Secluded dark matter; Gamma-rays; Antiprotons